E(x)=![( x^{4} + 7x^{3} ): x^{2} - x^{2} ( x^{4} + 7x^{3} ): x^{2} - x^{2}](https://tex.z-dn.net/?f=%28+x%5E%7B4%7D+%2B+7x%5E%7B3%7D+%29%3A+x%5E%7B2%7D+-+x%5E%7B2%7D+)
Dau coroana!
Răspunsuri la întrebare
Răspuns de
1
[tex] (x^{4} +7 x^{3} ): x^{2} - x^{2}= \\ \frac{ x^{4} }{ x^{2} } + \frac{7 x^{3} }{ x^{2} } - x^{2} =
x^{2} +7x- x^{2} =7x[/tex]
BlueSquare:
Mersi mult
Alte întrebări interesante
Limba română,
9 ani în urmă
Chimie,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
10 ani în urmă
Matematică,
10 ani în urmă